2005
DOI: 10.1111/j.1439-0388.2005.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

The FUT1 and ESR genes – their variability and associations with reproduction in Přeštice Black‐Pied sows

Abstract: The determination of genetic variability by means of molecular genetic markers FUT1 and ESR2, and the evaluation of their associations with reproduction traits in population of Prestice Black-Pied sows have been implemented. A lower frequency of the allele FUT1A than the frequency of the allele FUT1G in the FUT1 gene was ascertained. In the ESR2 polymorphism, a higher frequency of the allele ESR2A compared with the allele ESR2B was determined. In the second to sixth litters as well as in the first to sixth lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Actually, the FUT1 gene has been determined as a candidate gene for the Escherichia coli F18 receptor locus (MEIJERINK et al, 1997) and an association with oedema disease, diarrhea, and thus an association with animal health was severalfold observed. Because animal health is strongly attended with fecundity, FUT1 could also serve as a candidate gene for litter size in swine (HORÁK et al, 2005). Concerning estrogen receptors, there are at least two different classes, and MUÑOZ et al (2004) mapped the estrogen receptor 2 (ESR2) gene at the telomeric end on the q arm of SSC1 in contrast to the ESR1 gene, which is located at the telomeric end on the p arm of SSC1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the FUT1 gene has been determined as a candidate gene for the Escherichia coli F18 receptor locus (MEIJERINK et al, 1997) and an association with oedema disease, diarrhea, and thus an association with animal health was severalfold observed. Because animal health is strongly attended with fecundity, FUT1 could also serve as a candidate gene for litter size in swine (HORÁK et al, 2005). Concerning estrogen receptors, there are at least two different classes, and MUÑOZ et al (2004) mapped the estrogen receptor 2 (ESR2) gene at the telomeric end on the q arm of SSC1 in contrast to the ESR1 gene, which is located at the telomeric end on the p arm of SSC1.…”
Section: Introductionmentioning
confidence: 99%
“…One marker, which is used in commercial pig production, is the estrogen receptor gene 1 (ESR1), and ROTHSCHILD et al (1996) were the first who observed an association between ESR1 genotypes and litter size in swine. However, so far, there are a lot of inconsistent studies with regard to influence on the ESR1 gene on fecundity parameters in swine (SHORT et al, 1997;DEPUYDT et al, 1999;DRÖGEMÜLLER et al, 1999;KMIEĆ et al, 2002;GIBSON et al, 2002; VAN RENS and VAN DER LENDE, 2002;MATOUŠEK et al, 2003;GOLIÁŠOVÁ and WOLF, 2004;HORÁK et al, 2005;HOROGH et al, 2005;WANG et al, 2006). Therefore, additional candidate genes with potential influence on litter size are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Matoušek (2013) reported that the sows of PBP should reach 11 live-born piglets and 9.6 reared piglets per litter. Horák et al (2005) found 11.84 piglets in total, 10.88 live-born and 9.44 reared piglets per litter in PBP sows. It is evident from the achieved results, that the reproductive performance increased up to the 4th parity, which corresponds to the results described by Whittemore (2006), who state that fertility grows up to the 4th litter and then continuously drops.…”
Section: Resultsmentioning
confidence: 99%
“…Matoušek (2013) considers 165 days an optimal length of interval in PBP sows. Horák et al (2005) documented interval length between 165.58 -172.27 in their study.…”
Section: Resultsmentioning
confidence: 99%
“…It was recognized as a distinct breed in 1964, and since 1996 it has been bred in a closed population. Within that population, genetic markers in association with reproduction traits (Horák et al 2004, Horák et al 2005 and gene polymorphisms associated with meat performance traits (Zrůstová et al 2009) have been studied, but until recently semen quality had not been evaluated. Therefore, the objective of this study, conducted over a test period from 2001 to 2009, was to examine the semen quality parameters of the Přeštice black-pied breed while taking into account the potential effects of collection month and boar age.…”
Section: Introductionmentioning
confidence: 99%